Advanced diamond-reinforced copper composite coatings via cold spray and material characterization - Lupoi, Rocco; Yin, Shuo (My University, 2016)
Diamond reinforced copper matrix composites (DCMC) has great potentials for heat sinks applications due to their excellent thermal properties. Cold Spray, as a relatively emerging coating technique, is able to fabricate coatings or bulk materials at entire solidstate, significantly lowering the risk of oxidation, phase transformation and high thermal residual stress because of the low pr ocessing temperature. In this paper, thick DCMC coatings were fabricated via cold spray using copperclad diamond powder or its mixture with pure copper powder. It was found that cold spray due to its low processing temperature was able to avoid the graphitization of diamond in the DCMC coatings. Using the pure clad diamond powder only , the diamond in the original feedstock was almost completely retained in the coating which contained more than 40 wt.% diamond. Such high mass fraction of diamond has never been achieved in previous cold spray works using premixed powders. The mechanically mixed powder of clad diamond and copper also exhibited great retainbility for diamond; the diamond fraction in the coating was even larger than that in the original feedstock. Besides, the most important finding here is the additional copper powders acted as a buffer, effectively preventing the fracture of diamond in the coating.
International Thermal Spray Conference (ITSC)
PUBLISHED
Keywords: Cold Spray; DIAMOND; METAL MATRIX COMPOSITES; cold spray